Early life seizures in female rats lead to anxiety-related behavior and abnormal social behavior characterized by reduced motivation to novelty and deficit in social discrimination - Castelhano, Adelisandra Silva Santos; Ramos, Fabiane Ochai; Scorza, Fulvio Alexandre; Cysneiros, Roberta Monterazzo (Journal of Neural Transmission, 2015)
Previously, we demonstrated that male Wistar rats submitted to neonatal status epilepticus showed abnormal social behavior characterized by deficit in social discrimination and enhanced emotionality. Taking into account that early insult can produce different biological manifestations in a gender-dependent manner, we aimed to investigate the social behavior and anxiety-like behavior in female Wistar rats following early life seizures. Neonate female Wistar rats at 9 days postnatal were subject to pilocarpine-induced status epilepticus and the control received saline. Behavioral tests started from 60 days postnatal and were carried out only during the diestrus phase of the reproductive cycle. In sociability test experimental animals exhibited reduced motivation for social encounter and deficit in social discrimination. In open field and the elevated plus maze, experimental animals showed enhanced emotionality with no changes in basal locomotor activity. The results showed that female rats submitted to neonatal status epipepticus showed impaired social behavior, characterized by reduced motivation to novelty and deficit in social discrimination in addition to enhanced emotionality.